Parents' Views About the Vaccination Program in Taiwan - Chia-Wan Tang; Shih-Hui Huang; Ken-Pen Weng; Luo-Ping Ger; Kai-Sheng Hsieh (Elsevier, 2011)
To investigate parents' views about new vaccines, we surveyed the attitudes and awareness toward immunization program among parents of children younger than 14 years in Taiwan. Methods: Parents of children were invited to complete a questionnaire in a tertiary referral medical center in Kaoshiung, southern Taiwan from 2006 to 2008. A total of 535 questionnaires were completed. We used descriptive data for the analysis of parents' views and attitudes toward the current vaccination program in Taiwan. Results: Of the 535 respondents, most parents (93%) did not think the current vaccination program was satisfactory. Few (approximately 8%) preferred self-paid vaccines. About 63% of parents believed that the new (self-paid) vaccines provided more protection, whereas 48% deemed them too expensive. The most popular reason for preferring the new vaccines was greater protection (73%). One-half of parents considered the new vaccines to be expensive. Regarding parental awareness of side effect of vaccination, fever was the most well known and of greatest concern (91%). Most parents (68%) had good awareness of conjugated pneumococcal vaccines, and only few (13%) had heard of the human papilloma virus vaccine. Most parental information of vaccines came from pamphlets at the hospital (56%). Conclusion: We found the awareness of parents about new vaccines to be insufficient. They also considered the new vaccines to be expensive.